Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find a polynomial function \( f(x) \) of the least degree with the given zeros, follow these steps:
1. Identify the given zeros:
- Zero at \( x = 3 \) with multiplicity 2.
- Zero at \( x = 4i \). Since the polynomial must have real coefficients, the complex conjugate \( x = -4i \) is also a zero.
2. Write the factors corresponding to each zero:
- For the zero at \( x = 3 \) with multiplicity 2: \((x - 3)^2\).
- For the zero at \( x = 4i \): \((x - 4i)\).
- For the zero at \( x = -4i \): \((x + 4i)\).
3. Combine all factors to form the polynomial:
Combine the factors to construct the polynomial:
[tex]\[ f(x) = (x - 3)^2 (x - 4i) (x + 4i) \][/tex]
4. Simplify the polynomial:
- First expand the complex conjugate pair product:
[tex]\[ (x - 4i)(x + 4i) = x^2 - (4i)^2 = x^2 - (-16) = x^2 + 16 \][/tex]
- The polynomial now is:
[tex]\[ f(x) = (x - 3)^2 (x^2 + 16) \][/tex]
5. Expand the remaining factor:
- Expand \((x - 3)^2\):
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
- Now multiply this with \(x^2 + 16\):
[tex]\[ f(x) = (x^2 - 6x + 9)(x^2 + 16) \][/tex]
6. Perform the final expansion:
- Multiply each term in the first polynomial by each term in the second polynomial:
[tex]\[ \begin{align*} f(x) &= x^2(x^2 + 16) - 6x(x^2 + 16) + 9(x^2 + 16) \\ &= x^4 + 16x^2 - 6x^3 - 96x + 9x^2 + 144 \\ &= x^4 - 6x^3 + 25x^2 - 96x + 144 \end{align*} \][/tex]
So, the polynomial of the least degree with the given properties is:
[tex]\[ f(x) = x^4 - 6x^3 + 25x^2 - 96x + 144 \][/tex]
1. Identify the given zeros:
- Zero at \( x = 3 \) with multiplicity 2.
- Zero at \( x = 4i \). Since the polynomial must have real coefficients, the complex conjugate \( x = -4i \) is also a zero.
2. Write the factors corresponding to each zero:
- For the zero at \( x = 3 \) with multiplicity 2: \((x - 3)^2\).
- For the zero at \( x = 4i \): \((x - 4i)\).
- For the zero at \( x = -4i \): \((x + 4i)\).
3. Combine all factors to form the polynomial:
Combine the factors to construct the polynomial:
[tex]\[ f(x) = (x - 3)^2 (x - 4i) (x + 4i) \][/tex]
4. Simplify the polynomial:
- First expand the complex conjugate pair product:
[tex]\[ (x - 4i)(x + 4i) = x^2 - (4i)^2 = x^2 - (-16) = x^2 + 16 \][/tex]
- The polynomial now is:
[tex]\[ f(x) = (x - 3)^2 (x^2 + 16) \][/tex]
5. Expand the remaining factor:
- Expand \((x - 3)^2\):
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
- Now multiply this with \(x^2 + 16\):
[tex]\[ f(x) = (x^2 - 6x + 9)(x^2 + 16) \][/tex]
6. Perform the final expansion:
- Multiply each term in the first polynomial by each term in the second polynomial:
[tex]\[ \begin{align*} f(x) &= x^2(x^2 + 16) - 6x(x^2 + 16) + 9(x^2 + 16) \\ &= x^4 + 16x^2 - 6x^3 - 96x + 9x^2 + 144 \\ &= x^4 - 6x^3 + 25x^2 - 96x + 144 \end{align*} \][/tex]
So, the polynomial of the least degree with the given properties is:
[tex]\[ f(x) = x^4 - 6x^3 + 25x^2 - 96x + 144 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.